Edukasi Aktivitas Fisik Pada Ibu Hamil Di Posyandu Dewi Ratih 1 Dengan Media Leaflet - Tiara Fatmarizka; Nabila Rizka Lathifani; Faradila Risky Adha; Fadhilla Mutiara Zahra; Sakhina Lancha Faliha; Revina Nanda Alya; Arif Pristianto (STIKes Ibnu Sina Ajibarang, 2023)
Pregnancy is a fetal development event that takes place approximately 9 months after fertilization. It is not uncommon for pregnant women to be reluctant to engage in physical activity due to a decline in physical condition and the understanding that physical activity is considered to be harmful to the womb. The partners for this service activity are pregnant women at Posyandu Dewi Ratih 1, Ngadirejo, Sukoharjo. This service activity aims to provide information to pregnant women about the importance of physical activity through non-pharmacological therapy in the form of exercise which can help smooth the birthing process. The educational method provided is in the form of lectures accompanied by leaflets containing physical activities for pregnant women. The pre-test and post-test aims to measure the level of understanding of this educational provision. Based on the results of the comparison of pre-test and post-test on 9 respondents, there was an increase in the average score from 0% to 44% in answering all questions correctly. In this service activity, there was an increase in the understanding of pregnant women at Posyandu Dewi Ratih 1 regarding the importance of physical activity during pregnancy using leaflets as media.